‘DON’T HATE ME BECAUSE I AM BEAUTIFUL’: A CHALLENGING CAREER IN SPA FOR STUDENTS WITH DISABILITIES (Proceedings of International Conference on Special Education, 2015)
People with disabilities faced numerous challenges as they leave school with lack of skills or qualification which results in unemployment. It is critical that these people are well prepared, to make the transition work successful, by effective assistance in making a good start in the world of employment which positively affect them professionally and gives personal success in the future stages of life. Since interest in physical wellness increases, spa therapy became popular and emerged as important profit centres for beauty salon, resorts and hotels. Many people have overlooked the potential of people with disabilities in this field. The purpose of this study was to fill the gap by identifying different and more challenging market segments for people with disabilities. This research was carried out using case study involving 15 students with disabilities in Panji Secondary School. The participants were observed during their training and the way they carried out the task of performing the facial treatment, hand and foot spa at the site. This research paper revealed some interesting facts about the skills in spa field that can enhance an individual’s self-confidence. Out of 15 participants, 8 students have been equipped with the skills needed in spa services. Most people assumed typical people are expertise in beauty line, but with training, encouragement and commitment, people with disabilities do show equivalent qualities and talent. The results of this study support the effectiveness of the spa skills amongst the people with disabilities focusing on practical, hands-on learning, with more direct relevance to their career aspirations. It also supports the findings that people with disabilities can overcome barriers successfully.